The Effect of 30 Minutes of Light Walking on Decreasing Blood Sugar Levels in Elderly People with Type 2 Diabetes Mellitus (Dukuh Village, Gondang District, Tulungagung Regency): Pengaruh Jalan Kaki Ringan 30 Menit Terhadap Penurunan Kadar Gula Darah Pada Lansia Penderita Diabetes Melitus Tipe 2 (Desa Dukuh Kecamatan Gondang Kabupaten Tulungagung) - Riawan, Asep Wahyu; Farida, Farida; Yitno , Yitno (Universitas Muhammadiyah Sidaorjo, 2024)
A person with old age will experience decreased organ function, as well as sensitivity to insulin. WHO data in 2011 found the world population who suffer from Diabetes Militus increase every year, this is because of low knowledge in managing healthy lifestyle, so it is necessary to do lifestyle management activity of elderly to lower blood sugar level. This study aims to determine the effect of mild walking 30 minutes to lower blood sugar levels diabetes mellitus type 2.The design used in this research is pre experiment One-Group Pre-post Test Design. The population in this study is elderly suffer of diabetes mellitus type 2 in Dukuh village conducted on May 19, 2017, using purposive technique with a total of 24 respondents. Data retrieval with light treatment 30 minutes. Then the data processed with Editing, Coding, Scoring and Tabulating techniques and tested with Wilcoxon Sign Rank Test statistics. Before the procedure was light 30 minutes from 24 respondents Most had random blood sugar level in the category of diabetes that is 20 respondents (83%), after a light treatment 30 minutes most of the respondents had random blood sugar level in the category of diabetes that is 14 respondents. (58.3%). The results showed that there was a 30 minute light walking exercise effect to lower blood glucose levels in elderly people with type 2 diabetes mellitus shown by p value = 0,000 and α = 0.05 which means value (p≤0,05). Therefore, researchers believe that a mild treatment of 30 minutes is very important for people with type 2 diabetes mellitus so that proven to lower blood sugar levels in people with diabetes mellitus.